A Gas Chromatographic Method for the Determination of Bicarbonate and Dissolved Gases - Loughrin, John H.; Antle, Stacy W.; Polk, Jason (Frontiers in Environmental Science, 2017)
A gas chromatographic method for the rapid determination of aqueous carbon dioxide and its speciation into solvated carbon dioxide and bicarbonate is presented. One-half mL samples are injected through a rubber septum into 20-mL vials that are filled with 9.5 mL of 0.1 N HCl. A one mL portion of the headspace is withdrawn and injected onto a gas chromatograph equipped with a thermal conductivity detector. Using the dimensionless Henry’s constant for carbon dioxide and an adaptation of the Henderson-Hasselbalch equation, carbon dioxide in the samples can be categorized among solvated, bicarbonate, and carbonate forms. Natural water samples as well as wastewater from a municipal sewage treatment plant and a swine rearing operation were analyzed by this method and the results compared favorably to those obtained by titration. Samples stored for up to five weeks showed no significant changes in carbon dioxide concentrations. In addition, using flame ionization and electron capture detectors, methane and nitrous oxide concentrations in the samples were also measured.